Sulfur removal from original and acid treated lignites by pyrolysis - ÖZDOĞAN, ZEYNEP SİBEL (ELSEVIER SCI LTD, 2006)
Six original, three hydrochloric acid treated and three demineralized lignite samples were pyrolysed at seven different temperatures between 350 and 950 degrees C for 7 thin under evolved gas atmosphere. All samples and their chars were analysed quantitatively for their total sulfur content and pyritic, sulfate and organic sulfur forms. The alkaline oxide contents of original lignites and their hydrochloric acid treated counterparts were determined. The results clearly indicate that calcium and sulfurous compounds in the parent lignites undergo various chemical changes during pyrolysis. The pyrolysis temperature, types of sulfur and calcium compounds, all affect the behaviour of sulfur during pyrolysis. Higher pyrolysis temperatures favour total sulfur removal for all lignites, reaching 30-54% around 850 and 950 degrees C. HCl treatment and demineralization decreases calcium contents, hence, increases quantitative sulfur removal froth the lignites by pyrolysis. The maximum total sulfur removal from acid treated lignites is observed as 77%. The ratios of the total sulfur to heating value decreases with increases of pyrolysis temperature up to around 600 degrees C for acid treated lignites and no major changes are observed at higher pyrolysis temperatures; no common behaviour is observed for original lignites. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: pyrolysis; sulfur removal; acid treatment; lignites; COAL PYROLYSIS; TURKISH LIGNITES; ORGANIC MATRIX; RANK COALS; DESULFURIZATION; BEHAVIOR; PYRITE; MATTER; FORMS; TRANSFORMATIONS